2021
DOI: 10.1016/j.jbc.2021.100996
|View full text |Cite
|
Sign up to set email alerts
|

HSP90 inhibition downregulates DNA replication and repair genes via E2F1 repression

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 71 publications
1
16
0
Order By: Relevance
“…It is widely acknowledged that DNA replication ensures that cellular genetic information is accurately copied and correctly transmitted to offspring cells [ 32 , 40 , 41 ]. However, DNA replication is prone to interference and damage under various pressures in the body, leading to stagnant DNA replication, affecting genome stability, and even inducing apoptosis [ 42 ], necrosis [ 43 ], and carcinogenesis [ 44 ]. Pathway enrichment analysis suggested that MAD2L1 affected the pathogenesis of proliferation and apoptosis in hepatocellular carcinoma via the above pathways.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely acknowledged that DNA replication ensures that cellular genetic information is accurately copied and correctly transmitted to offspring cells [ 32 , 40 , 41 ]. However, DNA replication is prone to interference and damage under various pressures in the body, leading to stagnant DNA replication, affecting genome stability, and even inducing apoptosis [ 42 ], necrosis [ 43 ], and carcinogenesis [ 44 ]. Pathway enrichment analysis suggested that MAD2L1 affected the pathogenesis of proliferation and apoptosis in hepatocellular carcinoma via the above pathways.…”
Section: Discussionmentioning
confidence: 99%
“…E2F1 has been attributed to numerous cancer hallmarks in prostate cancer, including cell cycle, proliferation and apoptosis [ 45 ], and its expression is so closely aligned with disease stage that it has been proposed as a potential biomarker [ 46 , 47 ]. Notably, AR, MYC and E2F1/2 are all established Hsp90 client proteins, and targeting Hsp90 inhibits expression of AR in prostate cancer (reviewed in [ 41 ]), and MYC [ 48 , 49 , 50 , 51 ] and E2F1 [ 52 , 53 ] in other cancers. Our ability to identify known pathways associated with Hsp90 and prostate cancer through omics analysis of PDE tissues highlights the capacity for omics identification of novel targets and biomarkers in the face of prostate tumor heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…By focusing on the differences between the heat stressed groups to evaluate the effect of HSP70 supplementation, we observed differences in the expression of three genes ( HSF1, HSP90AA1 and ATP1A1 ) that had a strong tendency towards significant downregulated in the H41 ( Figure 1 ). HSP90AA1 belongs to the family of HSP90 and encodes for a molecular chaperon, which participates in the proper folding of misfolded proteins using an ATPase activity; however, the protein is involved also in other functions, such as cell signalling, transcription and DNA replications and repair [ 74 , 75 ], yet they require excessive amounts of cellular energy to mitigate the negative effects of heat stress in cellular level. The roles of HSF1 and ATP1A1 are thoroughly discussed in the previous sections of the discussion.…”
Section: Discussionmentioning
confidence: 99%